The specificity of autobiographical memory in depressed and non-depressed participants - Eka Juliana (Kulliyyah of Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2007)
The present study attempts to explore the specificity of autobiographical memories in patients suffering from major depressive disorder. It particularly explores the process of autobiographical recollection and examines the knowledge retrieved by patients as well as normal participants. Previous studies indicated that the patients frequently produced summary accounts of categories of events while normal controls produced the description of specific events (Williams, 1996). Moreover, several studies also showed that depressed patients have considerable difficulties to move fluently through the hierarchy knowledge base (Williams & Dritschel, 1988). Quasi experimental design was used in this study. To analyse the memory description content analyses were used. Two groups of study, depressed participants and nondepressed participants, were compared by using independent T-test and Chi-Square. The dependent measures were retrieval time, length, the specificity of autobiographical memory and memory type (positive memory, negative memory, neutral memory and no memory). The rating scales were ‘importance’, ‘emotion intensity’ and ‘vividness’. The cue words paradigm with Malaysian Version and Beck Depression Inventory were administered to 13 depressed and 13 non-depressed participants. The result showed that depressed patients have significantly shorter in retrieval time than non-depressed participants. Depressed patients are significantly less elaborative in memory descriptions as compared to non-depressed participants. Depressed patients are significantly less specific and more categoric in memory descriptions than non-depressed participants. Depressed patients’ memories contain significantly more emotional components than the memories of their normal counterparts. The present study would have significant implications to the diagnostic and treatment decisions in clinical setting, and should therefore be explored at further length in future research autobiographical memory and clinical depression